PREVALENCE AND INTENSITY OF INTESTINAL PARASITIC WORM EGGS IN CATTLE FECES AT THE SLAUGHTERHOUSE IN TANAH MERAH VILLAGE, NORTH SAMARINDA DISTRICT - Hariani, Nova; Anggraeni, Dwi Ayu; Yuliatin, Ervinda; mukhlis, Mukhlis; Annisa, Sajidah Salsabila (Jurnal Pendidikan Matematika dan IPA, 2025)
Cattle farming is the most popular business for many people as a source of income because it producer meat and milk that has high economic value. Based on the maintenance aspect, cattle products produced in Indonesia have not been maximized due to many health problems of farm animals. One of the pathogens that are often found on farms is parasites. This can pose a real danger to some livestock. This study aims to determine the prevalence and intensity of intestinal parasitic worm eggs in cattle feces found in Tanah Merah Village Slaughterhouse, North Samarinda District. The total number of samples in the study was 30 cattle fecal samples. Worm eggs are observed through fecal examination using two methods, namely sedimentation method and flotation method. The results of this study showed that 13 types of intestinal parasitic worm eggs were found in cattle feces found from Tanah Merah Village Slaughterhouse, Samarinda, namely Ascaris lumbricoides, Bunostomum phlebotomum, Clonorchis sinensis, Dicrocelium dendriticum, Fasciola hepatica, Hymenelopsis nana, Paragonimus wastermani, Schistosoma bovis, Schistosoma mansoni, Schistosoma haemabotium, Strongyloides stecoralis, Taenia saginata and Trichuris trichura. Taenia saginata worm eggs have the highest intensity value of 1.028 eggs/individual. Ascaris lumbricoides worm eggs have the highest prevalence value of 26,67% of the total individuals.